2013
DOI: 10.4315/0362-028x.jfp-12-566
|View full text |Cite
|
Sign up to set email alerts
|

Survivability of Escherichia coli O157:H7 in Mechanically Tenderized Beef Steaks Subjected to Lactic Acid Application and Cooking under Simulated Industry Conditions

Abstract: Mechanical tenderization improves the palatability of beef; however, it increases the risk of translocating pathogenic bacteria to the interior of beef cuts. This study investigated the efficacies of lactic acid spray (LA; 5 % ), storage, and cooking on the survivability of Escherichia coli O157:H7 in mechanically tenderized beef steaks managed under simulated industry conditions. Beef subprimals inoculated with either high (10(5) CFU/ml) or low (10(3) CFU/ml) levels of E. coli O157:H7 were treated (LA or cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, E. coli O157:H7 was not detected on low inoculum (10 3 CFU ml −1 ) treated mechanically tenderized steaks cooked to varied internal temperatures (Chancey et al . ). Luchansky et al .…”
Section: Resultsmentioning
confidence: 97%
“…However, E. coli O157:H7 was not detected on low inoculum (10 3 CFU ml −1 ) treated mechanically tenderized steaks cooked to varied internal temperatures (Chancey et al . ). Luchansky et al .…”
Section: Resultsmentioning
confidence: 97%
“…The efficiency of lactate in inhibiting E . coli O157:H7 multiplication in food products and cattle hides is well documented [ 43 , 44 ]. Furthermore, Ogawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, similar trends with respect to recovered populations and transfer rates were obtained for the aerobic bacterial flora (Table 1). Deep tissue microbial contamination as a result of mechanical blade tenderization has been reported by a number of investigators (4,8,9,12,18,19,28). In agreement with our findings, Luchansky et al (18,19) reported that pathogen cell transfer rates were highest in the topmost 1 cm of beef subprimals subjected to blade tenderization.…”
Section: Effect Of Antimicrobial Spray Treatments On Surface Contaminmentioning
confidence: 94%